Brodalumab Versus Guselkumab in Patients with Moderate-to-Severe Psoriasis with an Inadequate Response to Ustekinumab: A Randomized, Multicenter, Double-Blind Phase 4 Trial (COBRA) - Kristian Reich; Luca Bianchi; Abdallah Khemis; Julia-Tatjana Maul; Athanasios Tsianakas; Christoph M. Schempp; Kim Petersen; Mia M. Noergaard; Lluis Puig (Adis, Springer Healthcare, 2024)
Abstract Introduction Despite improved treatment options for plaque psoriasis within the last decades, some patients still have an inadequate response to treatment. Direct clinical evaluation between therapies used after biologic failure could facilitate physicians' choice of treatment. Methods COBRA (NCT04533737) was a randomized (1:1), blinded (patient and assessor), 28-week, active-comparator trial conducted in Europe from December 2020 to December 2022. The objective was to compare the efficacy and safety of brodalumab versus guselkumab in adults with moderate-to-severe plaque psoriasis and inadequate response to ustekinumab. Patients received either brodalumab 210 mg or guselkumab 100 mg. The primary [having Psoriasis Area and Severity Index (PASI)-100 response at week 16] and key secondary (time to PASI-100 response) endpoints were tested in a fixed sequence. Results Due to delays and enrollment challenges, recruitment was terminated with 113 patients enrolled of 240 planned. The proportion of patients having PASI-100 at week 16 for brodalumab was 53.4% compared with 35.9% for guselkumab [odds ratio (OR) 2.05; 95% confidence interval (CI) 0.95, 4.44; p = 0.069]. As this was not statistically significant, the hierarchical testing procedure was stopped. All other secondary PASI endpoints had nominal p-values below 0.05 in favor of brodalumab. In the time to PASI response analyses, brodalumab separated from guselkumab in estimated cumulative incidence of patients achieving a response from week 2 onward, suggesting fast onset of action with brodalumab. Quality of life measures improved in both treatment groups. The safety findings were consistent with the known safety profiles. Conclusions Brodalumab showed a tendency toward better and earlier effect than guselkumab in patients who had failed ustekinumab. Thus, this trial provides important information in assisting physicians in their choice of therapy for patients who have failed their prior anti-interleukin (IL)-12/23 treatment. Trial Registration ClinicalTrials.gov identifier NCT04533737.